Contradictions around reading. The ongoing yes but no - Sánchez-García, Sandra (Anuario ThinkEPI, 2022)
Although everyone considers reading to be a basic skill that any person should develop, especially those who are undergoing some kind of training, numerous studies show us a student profile that is not very motivated by the reading practice. These same studies present us with a context full of contradictions. On most occasions, what is desirable is far from reality. In this paper, based on a series of evidence on reading, we would like to invite information and documentation professionals to reflect on some of these contradictions. Our only aim is to make visible a problem that seems to be deeply rooted in conformism and resignation, but on which many decisions can and must still be taken.